Comparison of Landing Biomechanics Between Male and Female Dancers and Athletes, Part 1: Influence of Sex on Risk of Anterior Cruciate Ligament Injury. (May 2014) - Orishimo, Karl F.; Liederbach, Marijeanne; Kremenic, Ian J.; Hagins, Marshall; Pappas, Evangelos
Background: The incidence of anterior cruciate ligament (ACL) injuries among dancers is much lower than among team sport athletes, and no clear disparity between sexes has been reported in the dance population. Although numerous studies have observed differences in landing biomechanics of the lower extremity between male and female team sport athletes, there is currently little research examining the landing biomechanics of male and female dancers and none comparing athletes to dancers. Comparing the landing biomechanics within these populations may help explain the lower overall ACL injury rates and lack of sex disparity. Hypothesis: The purpose was to compare the effects of sex and group (dancer vs team sport athlete) on single-legged drop-landing biomechanics. The primary hypothesis was that female dancers would perform a drop-landing task without demonstrating typical sex-related risk factors associated with ACL injuries. A secondary hypothesis was that female team sport athletes would display typical ACL risk factors during the same task. Study Design: Controlled laboratory study. Methods: Kinematics and kinetics were recorded as 40 elite modern and ballet dancers (20 men and 20 women) and 40 team sport athletes (20 men and 20 women) performed single-legged drop landings from a 30-cm platform. Joint kinematics and kinetics were compared between groups and sexes with a group-by-sex multivariate analysis of variance (MANOVA) followed by pairwise t tests. Results: Dancers of both sexes and male team sport athletes landed similarly in terms of frontal-plane knee alignment, whereas female team sport athletes landed with a significantly greater peak knee valgus ( P = .007). Female dancers were found to have a lower hip adduction torque than those of the other 3 groups ( P = .003). Dancers (male and female) exhibited a lower trunk side flexion ( P = .002) and lower trunk forward flexion ( P = .032) compared with team sport athletes. Conclusion: In executing a 30-cm drop landing, female team sport athletes displayed a greater knee valgus than did the other 3 groups. Dancers exhibited better trunk stability than did athletes. Clinical Relevance: These biomechanical findings may provide insight into the cause of the epidemiological differences in ACL injuries between dancers and athletes and the lack of a sex disparity within dancers.